Pengaruh Suhu Dan Waktu Distilasi Terhadap Komposisi Kimia Asap Cair Dari Kulit Durian - Widiya Widiya; Idral Idral; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Purification  of  liquid  smoke  is  very  important  for  the  safety  of  liquid  smoke  for preservative  food.  Distillation  was  done  reduces  carsinogenic  compound  such  as  tar  and benzo(a)pyrene and determined 1st, 2nd, 3th grade of smoke  liquid. The research was done using distillation process, with temperature and time variable. The results of GCMS analysis indicated no detected  tar and benzo(a)pyrene. Maximum  temperature  to get of  liquid smoke 1st  grade  at  125oC with  distillation  time was  30 minutes.  At  this  condition  value  of  acid, carbonyl  and  phenol  were  20.53%,  27.05%  and  0% Keywords: Pyrolysis, Distillation, Liquid Smoke